Maritime delimitation in the context of the disappearance of state territory due to climate change: Analysis of procedural and substantial legal issues of a not that hypothetical scenario (2015)
This article purports to analyze descriptively and theoretically the substantial and procedural legal issues derived from a potential litigation on maritime delimitation before the International Court of Justice in a scenario where the territory of one of the States concerned will inevitably disappear after the rendering of the judgment. This work complements the current literature with respect to the potential disappearance of Island-States due to climate change and sea level rise, and about the suitability of public international to provide a satisfactory answer. Together with a descriptive elucidation of the international law relevant to each of the legal issues addressed, the authors encourage Island-State to avail of maritime delimitation as a tool that may strengthen their current political and legal strategies for the preservation of their natural resources and independence notwithstanding the disappearance of their original territory.